Production of Arbutin by Biotransformation of Hydroquinone Using Peganum harmala, Varthemia persica and Pycnocycla spinosa Cell Suspension Cultures: Production of arbutin from hydroquinone - Asghari, Gholamreza; Ihsanpour, Aliakbar; Akbari, Azam; Akbari, Azam (Iranian Journal of Pharmaceutical Sciences, 2006)
Cell cultures of Varthemia persica, Peganum harmala and Pycnocycla spinosa have been studied to evaluate their abilities to bioconvert exogenous hydroquinone. Arbutin is an important substance that has several pharmaceutical applications; therefore, we have established V. persica and P. spinosa cultures which seem to be able to metabolize hydroquinone. Callus cultures of V. persica were established from seedlings, and healthy suspensions were grown using Murashige and Skoog medium supplemented with 2,4-D and kinetin. Exogenous hydroquinone was fed to cell suspension cultures and biotransformation reactions were detected over 24 h of incubation. The cultures then extracted with methanol and extracts subjected to TLC and HPLC analysis. The V. persica and P. spinosa cultured cells in this study seem to exhibit an ability in the glucosylation of hydroquinone to arbutin. No conversion was observed with P. harmala cell suspension cultures. The ability of cultured plant cells for biotransformation of substrates appears to be depended on the culture strains.